Karakteristik Kompetensi Guru Dari Perspektif Siswa - Larasati, Larasati; Mahatma, Mahatma (Jurnal Ilmiah Mandala Education (JIME), 2021)
The purpose of this research is to identify the characteristics of teacher competence that are preferred by the students or according to the students' point of view. This research was conducted from June to July 2021. The method used in this research is quantitative method with survey technique. The survey was conducted through a google form in the form of a questionnaire. There are 110 respondents who filled out the questionnaire in the study. In the research instrument grid, there are four research variables. The results of this study indicate that students prefer teachers who have professional competence, then the second is personality competence, the third is social competence, and the last is pedagogic competence. According to the student's perspective on pedagogic competence, the teacher is still lacking or good enough. So, for pedagogic competence, teachers must pay attention to or be more creative and innovative in the delivery of learning materials so that they can make the class more fun. This is due to several factors which will be discussed in the discussion.The purpose of this research is to identify the characteristics of teacher competence that are preferred by the students or according to the students' point of view. This research was conducted from June to July 2021. The method used in this research is quantitative method with survey technique. The survey was conducted through a google form in the form of a questionnaire. There are 110 respondents who filled out the questionnaire in the study. In the research instrument grid, there are four research variables. The results of this study indicate that students prefer teachers who have professional competence, then the second is personality competence, the third is social competence, and the last is pedagogic competence. According to the student's perspective on pedagogic competence, the teacher is still lacking or good enough. So, for pedagogic competence, teachers must pay attention to or be more creative and innovative in the delivery of learning materials so that they can make the class more fun. This is due to several factors which will be discussed in the discussion.